PERANCANGAN CERGAM “IBU KAMI SEEKOR KUCING” CERITA RAKYAT JAMBI - Ariska Ulandari; hendra afriwan (Universitas Negeri Padang, 2020)
The fairy tale of Our Mother is a Cat, none of the children have ever met the storybook in comical form. So that children are very less interested in reading it, because there is only writing and at least pictures so that it becomes less interesting. The comics in this book are intended as the main media to convey the contents of the moral message contained in the comics with an attractive visual appearance. The method used is the 4D method. 4D development model consists of four stages namely: Define, Design, Development and Dissemination. This comic book is assisted by other media such as wall clocks, tumbler, key chain, sticker, poster, flayers, , Instagram, cergam digital.Keywords: Book, Picture Story, Folk Story, Jambi.